Autosomal Dominant Hypocalcemia Type 1 and Neonatal Focal Seizures - Raluca Ioana Teleanu; Marlene Alexandra Sarman; Diana Anamaria Epure; Margarita Matei; Ioana Roşca; Eugenia Roza (MDPI AG, 2023)
Autosomal dominant hypocalcemia type 1 (ADH1) is a rare form of hypoparathyroidism that is characterized by gain-of-function mutations in the CASR gene, which provides instructions for producing the protein called calcium-sensing receptor (CaSR). Hypocalcemia in the neonatal period has a wide differential diagnosis. We present the case of a female newborn with genetic hypoparathyroidism (L125P mutation of CASR gene), hypocalcemia, and neonatal seizures due to the potential correlation between refractory neonatal seizures and ADH1. Neonatal seizures were previously described in patients with ADH1 but not in association with the L125P mutation of the CASR gene. Prompt diagnosis and management by a multidisciplinary and an appropriate therapeutic approach can prevent neurological and renal complications.